Simple Preparation of Pacific Cod Trypsin for Enzymatic Peptide Synthesis. (25th July 2011) - Fuchise, Tomoyoshi; Sekizaki, Haruo; Kishimura, Hideki; Klomklao, Sappasith; Nalinanon, Sitthipong; Benjakul, Soottawat; Chun, Byung-Soo
Abstract : Trypsin from the pyloric caeca of Pacific cod ( Gadus macrocephalus ) was easily prepared by affinity chromatography on Benzamidine Sepharose 6B and gel filtration on Superdex 75. Pacific cod trypsin was composed of three isozymes, and their molecular masses were estimated 23, 756.34 Da, 23, 939.62 Da, and 24, 114.81 Da by desorption/ionization time-of-flight mass spectroscopy (MALDI/TOF-MS) and their isoelectric points (pIs) were approximately 5.1, 6.0, and 6.2, respectively. The isolated Pacific cod trypsin showed high similarity to other frigid-zone fish trypsins. The kinetic behavior of tryptic hydrolysis toward N - p -tosyl-L-arginine methyl ester hydrochloride (TAME), N -benzoyl-L-arginine p -nitroanilide hydrochloride (BAPA), and p -amidinophenyl ester were also analyzed. In addition, the cod trypsin-catalyzed dipeptide synthesis was investigated using twelve series of "inverse subdtrates" that is p - and m -isomer of amidinophenyl, guanidinophenyl, (amidinomethyl)phenyl, (guanidinomethyl)phenyl, and four position isomers of guanidinonaphtyl esters derived from N -( tert -butoxycarbonyl)amino acid as acyl donor components. They were found to couple with an acyl acceptor such as L-alanine p -nitroanilide to produce dipeptide in the presence of the trypsin. All inverse substrates tested in this study undergo less enantioselective coupling reaction. The p -guanidinophenyl ester was most practical substrate in twelve series tested. The enzymatic hydrolysis of the resulting products was negligible.